2014
DOI: 10.5194/amt-7-437-2014
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving hurricane wind speeds using cross-polarization C-band measurements

Abstract: Abstract. Hurricane-force wind speeds can have a large societal impact and in this paper microwave C-band crosspolarized (VH) signals are investigated to assess if they can be used to derive extreme wind-speed conditions. European satellite scatterometers have excellent hurricane penetration capability at C-band, but the vertically (VV) polarized signals become insensitive above 25 m s −1 . VV and VH polarized backscatter signals from RADARSAT-2 SAR imagery acquired during severe hurricane events were compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 20 publications
(37 reference statements)
1
59
0
Order By: Relevance
“…Given the expense of hurricane evacuations and emergency preparations and the undermining effect of false alarms on population response, unnecessary hurricane warnings should be avoided. Recently, the analysis of RADARSAT-2 C-band SAR data and collocated wind measurements by the NOAA hurricane-hunter aircraft [7]- [11] has revealed that cross-polar scattering does not show any evident loss of sensitivity as the wind speed increases above 25 m/s, thus allowing accurate retrieval of strong to severe wind speeds. As a consequence, the use of cross polarization in addition to the most common VV or HH polarization becomes 0196-2892 © 2015 IEEE.…”
mentioning
confidence: 99%
“…Given the expense of hurricane evacuations and emergency preparations and the undermining effect of false alarms on population response, unnecessary hurricane warnings should be avoided. Recently, the analysis of RADARSAT-2 C-band SAR data and collocated wind measurements by the NOAA hurricane-hunter aircraft [7]- [11] has revealed that cross-polar scattering does not show any evident loss of sensitivity as the wind speed increases above 25 m/s, thus allowing accurate retrieval of strong to severe wind speeds. As a consequence, the use of cross polarization in addition to the most common VV or HH polarization becomes 0196-2892 © 2015 IEEE.…”
mentioning
confidence: 99%
“…In the meantime, much effort is devoted to developing cross polarization geophysical model functions (GMFs) for hurricane wind retrieval using polarimetric SAR imagery. Several of the GMFs assume a linear relationship between VH in dB and wind speed U10 van Zadelhoff et al, 2013van Zadelhoff et al, , 2014. One drawback of these GMFs is the lack of incidence angle () dependence, at least for the high wind range (U10>21 m/s).…”
Section: Introductionmentioning
confidence: 98%
“…The result prompts the incorporation of VH channel in the next generation scatterometer designs for extending the retrieved wind speed range (Lin et al 2012;Belmonte Rivas et al, 2014). In the meantime, much effort is devoted to developing cross polarization geophysical model functions (GMFs) for hurricane wind retrieval using polarimetric SAR imagery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations